(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India, the largest democratic country of the world, has over 1.20 billion populations whose sex ratio is 1000-940 (as according to 2011 census Report) of male and female respectively. The sources of Indian democracy and its prosperity depends upon the level of education, economic condition, political consciousness and political participation of both male and female in national, state and at grassroots levels. Indian women have been able to prove their ability in the field of education, science and technology, arts and culture, games and sports, fashion technology, defense of the country and in many other fields. But in the field of politics the role of women is not satisfactory.